Utilization of Household Waste into Liquid Organic Fertilizer: Empowering Community Collaborated with Muhammadiyah Branch Office of Colomadu Karanganyar Indonesia - Suparti, S; Asngad, Aminah; Agustina, Lina; Astuti, Rina; Ambarwati, A; Astuti, Dwi Setyo; Musbita, Erma; Sari, Siti Kartika; Warsiti, W (Universitas Muhammadiyah Surakarta, 2022)
Waste is stuff that is useless, underused, or abandoned as a byproduct of a process. The amount of organic household waste produces new environmental concerns, thus there must be a method to reduce it, one of which is converting it into liquid organic fertilizer. Organic waste can be utilized as a raw material to make organic fertilizers (liquid fertilizer and compost), which farmers can use. A moist organic matter or organic material with high water content, such as fruit or vegetable residue, is an excellent source material for liquid fertilizer made from organic waste. The goal of this community service is to teach people how to make liquid organic fertilizer out of household garbage, to conduct NPK tests for liquid organic fertilizer (POC), and to offer training and packaging support for POC products women's farming group (KWT) Berkah Tani 2. As a result of this community service project, the KWT Berkah Tani 2 has gained experience in producing liquid organic fertilizer, which will aid in reducing organic waste in the Colomadu region attempting to sell POC items derived from organic garbage.